The role of dietary minerals in the development of atheroma - Ya. V. Polonskaya; E. V. Kashtanova (Российский кардиологический журнал, 2019)
The article presents an overview of foreign and domestic studies aimed to study the role of elemental imbalance in the development of cardiovascular pathology. The pathogenetically significant mechanisms of the influence of diselementosis on the development of atherosclerotic changes in the walls of blood vessels are discussed. Particular attention is paid to such elements as iron, copper, zinc, selenium, cadmium.